PROTECTING BAMBOO COLUMN FROM HUMIDITY WITH POROUS PEDESTAL FOUNDATION - Eugenius Pradipto; Syam Rachma Marcillia; Nabila Afif; Swari Dewanti Hamastuti; Natasha Nurul Annisa (DIMENSI (Journal of Architecture and Built Environment), 2019)
Bamboo has been used for a long time as a material for simple to complex structures. Many advantages of bamboo as a building material makes it suitable for buildings in disaster-prone areas. Bamboo is however prone to humidity, which could cause fungi and moss to emerge and endanger the building structure. Pedestal foundation made of concrete or stone is often used to reduce this risk as for its action as a barrier of direct contact between soil and bamboo. Nevertheless, water from damp soil or rainwater can still penetrate the foundation by capillary transmission through the foundation’s pores. This research proposed a hollow pedestal foundation model with larger pores and compared its ability to reduce moisture on bamboo columns to an ordinary pedestal foundation. The case study is a temporary post-disaster housing project of 13 houses in Muntilan, Central Java, Indonesia, which was built on an active rice field. Visual examination showed that after 5 years of occupancy, bamboo houses built on hollow pedestal foundations still firmly stood without apparent attacks of fungi or overgrowing mold, whereas the moisture measurement showed that the usage of hollow pedestal foundation could reduce the humidity level in the bamboo column almost twice as fast compared to solid pedestal foundation.